The program assessment rating tool and the government performance and results act: evaluating conflicts and disconnections - Gueorguieva, Vassia et al. (2009)
This article looks at the Government Performance and Results Act (GPRA) and the Program Assessment Rating Tool (PART) and how they assess seven programs. It establishes that the PART does not adequately consider different program types and has characteristics that create a disconnection between this tool and the GPRA: It does not enter into dialogue with the GPRA regarding the choice of performance indicators; it evaluates programs through criteria that conflict with the programs' statutes or intent and penalizes programs for the degree of explicitness in their authorizing statutes; it uses standardized measures that sometimes overlook the intent of statutes or the discretionary nature of implementation; it employs a different level of analysis from the GPRA; it places a contradictory emphasis on the relationship between programs with similar goals; and it emphasizes different external factors influencing program performance. The article concludes with recommendations on how to improve the PART. - Reproduced.
Keywords: Public administration